Drainage Vein Induced Hydrocephalus Caused by an Unruptured Arteriovenous Malformation in an Adult Presenting with Visual Loss - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2014)
Arteriovenous malformations (AVMs) commonly present with seizures and hemorrhage. Hydrocephalus associated with an unruptured AVM in an adult patient is exceedingly rare. A 37-year-old male patient presented with total visual loss in his right eye and severe impairment in his left eye. His evaluation showed an unruptured right frontal AVM and bilaterally dilated lateral ventricles. The major draining vein of the AVM was obstructing the third ventricle. An urgent external ventricular drainage was used as the first line intervention and followed with a ventriculoperitoneal shunt two days later. His definitive treatment for AVM was staged stereotactic gamma-knife radiosurgery. Unruptured AVMs in adult patients may rarely cause hydrocephalus. Visual loss caused by such a hydrocephalus has not been reported before. Both communicating and non-communicating type hydrocephalus can be seen with unruptured AVMs, and have different pathophysiological mechanisms. Our patient was treated with ventriculoperitoneal shunting, and visual examination remained unchanged after the operation. Visual loss caused by hydrocephalus associated with an unruptured AVM in an adult patient has not been reported before. It may indicate an association of different pathophysiological mechanisms. The treatment must depend on the neurological condition of the patient.
Keywords: Adult; Arteriovenous malformation; Hydrocephalus; Unruptured; Visual loss